A systematic review of cognitive assessment in physical activity research involving children and adolescents. Issue 8 (August 2020) - Wade, Levi; Leahy, Angus; Lubans, David R.; Smith, Jordan J.; Duncan, Mitch J.
Abstract: Objectives: To summarise the reporting, administrative requirements and psychometric properties of cognitive measures used in experimental physical activity research conducted with school-aged youth. Design: Systematic review. Methods: Five databases (CINAHL, SPORTDiscus, Medline, Embase, and Psychinfo) were searched from inception to October, 2018. Studies meeting the following criteria were eligible for inclusion: experimental study design; apparently healthy youth aged 5–18 years; use of physical activity; and use of a performance-based cognitive test. Reporting, administration requirements, reliability, and validity of the included cognitive measures was extracted. Results: Included studies (n = 109) used 60 unique cognitive tests. Across the 109 included studies, a total of 181 tests were reported on. Test format (e.g. pen and paper, computer) was specified for 166 (91.7%); administration type (individual or group) for 108 (59.7%); and administration time for 49 (27.1%) of the tests. Of the 181 tests reported on, 72 (39.8%) provided information on either test–retest reliability or internal consistency, and 82 (45.3%) provided at least one form of test validation. Conclusions: A lack of reporting of test administration time, as well as information on the reliability and validity of included cognitive tasks are notable limitations of studies included in this review. Agreement on a smaller number of tests should be sought to improve the interpretability of future research. The summary provided by this systematic review can be used to inform the selection of performance-based cognitive measures in future physical activity research.